Pengaruh Endorsement Selebriti Instagram terhadap Minat Beli Remaja Putri - Gayatri Hutami Putri; Bhina Patria (Faculty of Psychology, Universitas Gadjah Mada, 2018)
Purchase intention is an initial stage in which consumers feel attracted to a product or service that will cause the desire to purchase as the final stage in making purchasing decisions. The occurrence of purchase intention is influenced by many factors one of which is a form of promotion by business owners. Promotion that is rampant in the social media Instagram is endorsement done by Instagram Celebrities. The purpose of this study is to determine whether there is influence of the endorsement by Instagram Celebrities to the purchase intention of young women. Researchers use the scale of purchase intention that has been modified. Subjects in this study were 73 female adolescence. This study used experimental group and control group to know difference of influence of endorsement by Instagram Celebrities. The resulting data will be analyzed using SPSS program. The results of this study showed a t-test score of 0.950 and p-value= 0.345 (p>0,05) which means there is no significant difference between the experimental group and the control group.